Anticoagulation before cardioversion of acute atrial fibrillation in the emergency department. Issue 4 (23rd March 2005) - Potier, Katherine; Parris, Richard
Abstract : A short cut review was carried out to establish whether anticoagulation is indicated prior to emergency department cardioversion of a patient with acute onset atrial fibrillation. 54 papers were found using the reported search, of which none presented any evidence to answer the clinical question. It is concluded that there is no evidence available to answer this question. Further research is needed.